2014
DOI: 10.2337/dc14-0761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 Weeks of Overfeeding on Ectopic Fat Deposition and Insulin Sensitivity: Testing the “Adipose Tissue Expandability” Hypothesis

Abstract: OBJECTIVEThe presence of large subcutaneous adipocytes in obesity has been proposed to be linked with insulin resistance and type 2 diabetes through the “adipose tissue expandability” hypothesis, which holds that large adipocytes have a limited capacity for expansion, forcing lipids to be stored in nonadipose ectopic depots (skeletal muscle, liver), where they interfere with insulin signaling. This hypothesis has, however, been largely formulated by cross-sectional findings and to date has not been prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 38 publications
8
92
2
1
Order By: Relevance
“…In contrast to a previous report (9), insulin sensitivity was not altered by the high-fat diet or VSL#3 treatment in the present study. Our observation is consistent with some (22,35) but not all (23,(36)(37)(38) previous studies. Nevertheless, the reason(s) for this discrepancy is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…In contrast to a previous report (9), insulin sensitivity was not altered by the high-fat diet or VSL#3 treatment in the present study. Our observation is consistent with some (22,35) but not all (23,(36)(37)(38) previous studies. Nevertheless, the reason(s) for this discrepancy is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in agreement with the current hypothesis that the presence of small subcutaneous adipocytes protects against insulin resistance and metabolic diseases. However, the study by Johannsen et al [31] showed opposite results. They studied the effect of 8 weeks of excess energy and lipid intake on adipocyte size and expansion in young healthy men: lean subjects with smaller adipocytes responded with a rapidly and not protective adipocyte remodelling, and despite expansion of subcutaneous fat they developed insulin resistance and released more inflammatory markers while subjects with larger subcutaneous adipocytes had less insulin resistance and visceral fat accumulation, maybe due to reduced expandability of these cells [31].…”
Section: When Adipocytes Become Dysfunctionalmentioning
confidence: 40%
“…However, the study by Johannsen et al [31] showed opposite results. They studied the effect of 8 weeks of excess energy and lipid intake on adipocyte size and expansion in young healthy men: lean subjects with smaller adipocytes responded with a rapidly and not protective adipocyte remodelling, and despite expansion of subcutaneous fat they developed insulin resistance and released more inflammatory markers while subjects with larger subcutaneous adipocytes had less insulin resistance and visceral fat accumulation, maybe due to reduced expandability of these cells [31]. It is likely that other factors are involved, possibly a genetic predisposition to type 2 diabetes or in general to ectopic fat deposition [3], [35], [37], [38].…”
Section: When Adipocytes Become Dysfunctionalmentioning
confidence: 40%
See 2 more Smart Citations